Antibiotic pollution and associated antimicrobial resistance in the environment - Barathe, Pramod; Kaur, Kawaljeet; Reddy, Sagar; Shriram, Varsha; Kumar, Vinay (Journal of hazardous materials letters, 2024)
The widespread and injudicious usage of antibiotics to contain pathogenic microbial infections, coupled with inadequate treatment of wastes containing non-metabolized antibiotics and their residues is resulting in rising environmental antibiotic concentrations, leading to ‘antibiotic pollution’. Antibiotic pollution is an emerging global challenge as it is proving a major driver for antibiotic- or antimicrobial-resistance (ABR/ AMR) with escalating ramifications worldwide, precipitating a surge in human morbidity. The extensive administration of antibiotics across domains such as human healthcare settings, agriculture, and aquaculture farming endangers the presence of antibiotics in diverse matrices including water, soil, and air. As a result, this dissemination significantly leads to the development of antibiotic resistance in the profuse sectors of the environment further provoking consequential health implications at different trophic levels. Owing to its significance, and to mitigate antibiotic pollution and its subsequential AMR, governmental guidelines and regulations are implemented across the globe to cultivate public awareness as concerted efforts for addressing this global predicament. Given the insufficient attention to the growing antibiotic pollution issues, prompt efforts must be taken to contemplate current circumstances and the rigor of the ongoing research. In this review, we endeavor to elucidate the escalation of antibiotic concentration and antibiotic-driven AMR in water, air, and soil environments with potential public health threats. Further, it focuses on various strategies and interventions to attenuate antibiotic pollution and mitigate its adverse impacts on the healthcare infrastructure, highlighting the success stories, challenges, and future directions. [Display omitted] •Antibiotic consumption for human health, hygiene and other sectors is on the rise.•Non-metabolized antibiotics or their residues are released into the environment.•Antibiotic pollution is turning out to be the leading cause of antimicrobial resistance (AMR).•Newer technologies and strategies needed for containing antibiotic pollution and AMR.